A contabilidade hídrica do Brasil: um ajuste das contas nacionais ambientais - Almeida, Vinicius Pacheco de (2017)
The objective of this work is to analyze the use of water in the Brazilian economy and how public agents can form more effective actions to optimize this natural resource in the Brazilian economy. For this, it is necessary to observe the adjusted Brazilian environmental GDP in the period from 2007 to 2012, which according to the methodology created and used by the UN SEEA gravitates alongside the 'traditional' GDP and complements the economic accounting of a country with sustainability, also seen In the national literature by Young (2003). For the measurement of national water accounting, it was necessary to compile the water use data for to made water of recourse and physic use table, through the IBGE, ANA and SNIRH and its national environmental product, the data used were extracted from the SNIRH and IPEA, a statistical adequacy was adjusted according to the environmental accounts of the SEEA for the reality of data available in Brazil, in order to form a historical series of environmentally adjusted GDP and the use of physical water flow. The results showed that over the years studied, physical use of water increased and adjusted GDP accompanied the growth of "traditional" GDP, but water treatment costs also increased over the period.